A Rising Tide: The Growing Nuclearisation of the Indian Ocean - Hughes, Lindsay (Curtin University, 2021)
"This dissertation examines why the Indian Ocean is becoming, increasingly, the locus of nuclear weapons and platforms. It establishes a nexus between Realism, the desire of states to maximise their power, the role of nuclear weapons in that quest, Seapower, and the importance of the Indian Ocean to the US, China, Pakistan and India. It demonstrates that the Indian Ocean is becoming nuclearised because of the confluence of its growing strategic importance and that nexus."